2018
DOI: 10.1038/s41593-018-0225-y
|View full text |Cite
|
Sign up to set email alerts
|

Restoring wild-type-like CA1 network dynamics and behavior during adulthood in a mouse model of schizophrenia

Abstract: Schizophrenia is a severely debilitating neurodevelopmental disorder. Establishing a causal link between circuit dysfunction and particular behavioral traits that are relevant to schizophrenia is crucial to shed new light on the mechanisms underlying the pathology. We studied an animal model of the human 22q11 deletion syndrome, the mutation that represents the highest genetic risk of developing schizophrenia. We observed a desynchronization of hippocampal neuronal assemblies that resulted from parvalbumin int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 73 publications
5
49
0
Order By: Relevance
“…Notably, enrichment in parvalbumin positive neurons ("Inhibitory PV") also reaches significance. This inhibitory PV neuron observation echoes a recent study demonstrating that treatment of PV inhibitory neurons in a mouse model of schizophrenia resulted in amelioration of disease phenotypes (Marissal et al 2018). Beyond the cortex, we detect strong enrichment in Drd1 positive medium spiny neurons ("Inhibitory MSN*").…”
Section: Cd8 T−cells Human Cd8 T−cells Cd4 T−cells Human Cd4 T−cellssupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, enrichment in parvalbumin positive neurons ("Inhibitory PV") also reaches significance. This inhibitory PV neuron observation echoes a recent study demonstrating that treatment of PV inhibitory neurons in a mouse model of schizophrenia resulted in amelioration of disease phenotypes (Marissal et al 2018). Beyond the cortex, we detect strong enrichment in Drd1 positive medium spiny neurons ("Inhibitory MSN*").…”
Section: Cd8 T−cells Human Cd8 T−cells Cd4 T−cells Human Cd4 T−cellssupporting
confidence: 88%
“…We obtained publicly available ATAC-seq data derived from lineage identified cell-types sorted ex vivo from mice and from mouse brain single nuclei analyses (Table S1) (Preissl et al 2018;Matcovitch-Natan et al 2016;Gray et al 2017;Mo et al 2015;Hughes et al 2017;Hosoya et al 2018;McClymont et al 2018). In total, we obtained 25 mouse ATAC-seq datasets encompassing subclasses of six broader cell types (dopaminergic neurons, excitatory neu-rons, glia, inhibitory neurons, retina cells, and T-cells) (Table S1).…”
Section: A Uniform Pipeline For Processing Of Mouse Atac-seq Datamentioning
confidence: 99%
“…The transient increase of parvalbumin interneuron activity with pharmacological approaches (diazepam) or with approaches that employ synaptogenic molecules to increase synaptic excitatory input onto PV cells—through exogenous application of Neuregulin1, a ligand of the interneuron-specific transmembrane receptor ErbB4—prevent OD plasticity after visual monocular deprivation (Kuhlman et al, 2013 ; Sun et al, 2016 ). Pharmacological or chemogenetic approaches that increase PV interneuron activity have also been shown to restore control-like neural activity (CA1 network dynamics) and behavior (cognitive function) in different mouse lines modeling mutations associated to schizophrenia (Marissal et al, 2018 ; Mukherjee et al, 2019 ).…”
Section: Manipulating Critical Periods To Shift Developmental Trajectmentioning
confidence: 99%
“…Sensoryevoked gamma oscillations from cortical in vivo recordings and synchronized, phase-locked firing of pyramidal cells, indicate entrainment of excitatory neurons to rhythmic inhibitory activity (Fries et al, 2001, Hasenstaub et al, 2005, Cardin et al, 2009, Gray et al, 1989. Because gamma oscillations are thought to control the synchronization of pyramidal cells (Marissal et al, 2018, Cardin, 2018, Buzsaki and Wang, 2012, Cardin et al, 2009), a reduced PV activity would result in a lack of generated gamma oscillations (Roux and Buzsaki, 2015), which in turn gives rise to asynchronous firing of pyramidal cells. This hypothesis has been recently confirmed by Marissal and colleagues, which found that DREADD-induced suppression of PV activity results in reduced inhibition of pyramidal neurons and leads to their mass desynchronization (Marissal et al, 2018).…”
Section: Activated Excitatory Dreadd In Wildtype Mice and Inhibitorymentioning
confidence: 99%
“…Because gamma oscillations are thought to control the synchronization of pyramidal cells (Marissal et al, 2018, Cardin, 2018, Buzsaki and Wang, 2012, Cardin et al, 2009), a reduced PV activity would result in a lack of generated gamma oscillations (Roux and Buzsaki, 2015), which in turn gives rise to asynchronous firing of pyramidal cells. This hypothesis has been recently confirmed by Marissal and colleagues, which found that DREADD-induced suppression of PV activity results in reduced inhibition of pyramidal neurons and leads to their mass desynchronization (Marissal et al, 2018). Moreover, they showed that increasing the inhibition of pyramidal neurons in wildtype mice, thus shifting the E:I towards inhibition, has no effect on neural synchronization, in-vitro network dynamics or behaviour.…”
Section: Activated Excitatory Dreadd In Wildtype Mice and Inhibitorymentioning
confidence: 99%